Vodní měkkýši bývalého lomu Chabařovice v severních Čechách - Luboš Beran (Malacologica Bohemoslovaca, 2010)
This paper completes the knowledge of aquatic molluscs of a former coal quarry Chabařovice near Ústí nad Labem in Northern Bohemia. This quarry was opened in 1977 and 20 years later the mining was finished. A part of the coal quarry was flooded and new water reservoir Milada originated in the area of 250 ha with max. depth 24,7 m and this water reservoir is the biggest aquatic habitat in this area. Other four smaller water reservoirs, numerous drainage canals and small wetlands were built and aquatic molluscs of these sites were studied in 2010. Altogether, 16 species of aquatic molluscs (12 gastropods, 4 bivalves) were found at 41 sites. Drainage canals, new brooks and small new wetlands are inhabited by poor aquatic malacofauna which contains often only one or two widespread species – Galba truncatula and Radix auricularia. Bivalve Pisidium casertanum was found only at three sites. Similar situation is in the case of water reservoirs Rabenov and Roudníky. Only artifical water reservoir Milada and smaller water reservoir close to this lake are inhabited by rich aquatic malacofauna containing 14 respectively 6 species. Molluscs were studied also in the past before opening the quarry and the actual malacofauna is richer probably due to the existence of more aquatic habitats. Three non-native species were found and the occurrence of other non native species is expected in the future as well as changes in autochtonous malacofauna.